Effect of Money Supply on Stock Market Development in Nigeria (1985–2023) - Stephen, Mathew; Akobi, Clement; Idi, Danjuma; Yusuf, Shadrach (Darul Yasin Al Sys, 2025)
This study investigates the impact of money supply on stock market development in Nigeria over the period 1985 to 2023, with a focus on assessing the differential effects of monetary aggregates and policy rate dynamics. Using annual time-series data obtained from the Central Bank of Nigeria (CBN) Statistical Bulletin, the analysis models stock market development proxied by total annual market capitalization as a function of narrow money supply (M1), broad money supply (M2), and the monetary policy rate (MPR). Multiple regression analysis was employed to test the formulated hypotheses, with standard diagnostic tests confirming the validity of the model, including the absence of multicollinearity and the normal distribution of residuals. Results reveal a statistically significant negative relationship between the monetary policy rate and stock market development (p < 0.05), suggesting that higher interest rates hinder capital market performance. In contrast, neither M1 nor M2 exhibited statistically significant effects (p > 0.05), indicating a limited influence of money supply aggregates on stock market growth within the observed period. These findings imply that interest rate adjustments remain a critical monetary policy tool in shaping investor behavior and capital market performance. The study recommends that policymakers prioritize interest rate management within a coherent monetary policy framework to foster a conducive environment for capital market development and broader economic growth.